SP0144 Residential workshop for parents of adolescents with juvenile idiopathic arthritis: a preliminary evaluation. (1st June 2001) - Turner, AP; Barlow, JH; Wright, CC
Abstract : Background: Caring for a child who has a chronic health condition can be a difficult and demanding task. Research has shown that some parents are at an increased risk for psychosocial problems. Objectives: The purpose of this study was to evaluate the effectiveness of a pilot Workshop designed specifically for parents of children with JIA. Method: 26 parents attended the two-day residential Workshop. The Workshop aimed to provide opportunities for parents to meet and discuss issues pertinent to caring for a disabled child. The Parents of Children With Disabilities Inventory (PCDI) was used to assess perceived disability-related stress. The PCDI comprises 4 subscales: Medical and Legal Concerns, Concerns for the Child, Concerns for the Family, Concerns for the Self. Higher scores indicate greater frequency and worry. Results were compared against a Comparison Group (CG) of 28 parents who expressed an interest in but did not attend the Workshop. Results: Median decreases in scores were significantly greater for the Workshop Group (WG) compared with the CG for Concerns for the Self (frequency) and Total frequency scores, (p = 0.020, 013, respectively). For the WG there were significant group decreases over time for Concerns for the Child (worried), Concerns for the Self (frequency), Total frequency score and Total worried score, (p = 0.023, 0.044, 0.031, 0.009, respectively). Conclusion: The finding of statistically significant improvements across a range of parental concerns is encouraging. Workshops for parents of children with JIA appear worthy of continued development and evaluation.